An Adaptive Intelligent Presentation Edugame for Fardu Ain Learning Using Production Rules Based on User Emotions - Rahmah, Mokhtar; Nor Azan, Mat Zin (2016)
An Edugame mobile application namely, Fardhu Ain Firdaus is an intelligent personalization edugame application for kids to learn Wudhu and Solah. This edugame used mobile platform that embedded the Production Rules intelligent technique for emotion prediction and presentation. The objectives of this research are to investigate limitation and parameter of adaptive rules based on emotions characteristics, to produce new rules for emotion solving in mobile edu games adaptive presentation and to test the accuracy of production rules for emotion solving in mobile edu games. The app interface will change according to the mood of the kids and ease their negative emotions and make the children ready to accept the learning and knowledge. This app can overcome "one size fits all" problem in app's games available by embedding the personalization into the apps. User acceptance tests have been done to 10 children, and results showed that this edugame app could enhance their understanding and attract them towards learning Fardhu Ain. This Edugame technology personalization application can be new attraction to the computer games' lover.